Inclusive Architecture: a neurocognitive approach - Solano Meneses, Eska Elena (Estoa. Journal of the Faculty of Architecture and Urbanism, 2021)
Inclusive architecture has hardly been considered under the substrate of neurocognitive sciences. Generally, this approach to architectural design is generated under functional guidelines that do not consider deeper levels such as neurocognitive ones. It is for this reason that the objective of this work is to analyze the implications of cognitive sciences in architectural design in order to propose design guidelines that contribute to strengthening inclusion in spaces through intuitive codes. To this end, it relies on an inductive method, which begins with an analytical review oriented to inclusive architecture, to contrast with the proposals from the neurocognitive sciences, accessibility, the principles of wayfinding and wayshowing and their semiotic foundations. It is concluded that, in the design of architectural spaces, it is necessary to consider spatial learning and thinking through patterns, since as seen, it is not the same as visual learning and thinking.